Unveiling Leukocyte Extracellular Traps in Inflammatory Responses of the Central Nervous System - Colciaghi, Francesca; Costanza, Massimo (Frontiers in Immunology, 2022)
Over the past nearly two decades, increasing evidence has uncovered how immune cells can actively extrude genetic material to entrap invading pathogens or convey sterile inflammatory signals that contribute to shaping immune responses. Originally identified in neutrophils, the release of decondensed chromatin fibers decorated with antimicrobial proteins, called extracellular traps (ETs), has been recognized as a specific form of programmed inflammatory cell death, which is now known to occur in several other leukocytes. Subsequent reports have shown that self-DNA can be extruded from immune cells even in the absence of cell death phenomena. More recent data suggest that ETs formation could exacerbate neuroinflammation in several disorders of the central nervous system (CNS). This review article provides an overview of the varied types, sources, and potential functions of extracellular DNA released by immune cells. Key evidence suggesting the involvement of ETs in neurodegenerative, traumatic, autoimmune, and oncological disorders of the CNS will be discussed, outlining ongoing challenges and drawing potentially novel lines of investigation.